ANALISIS KINERJA BADAN PERMUSYARATAN DESA TERHADAP KEPUASAN MASYARAKAT DESA CIKIJING KABUPATEN MAJALENGKA - OTONG KARYONO (DIALOGIKA, 2019)
During the reform era, the formation of the BPD was intended to improve the performance of the BPD, but in its implementation the performance of the BPD was not in line with community expectations and this was evidenced by the lack of socialization with the community. This study uses a verification research method with analytical techniques using simple linear regression analysis. The results showed that the performance of BPD was proven to have a positive and significant effect on community satisfaction. That is, BPD that has performance in accordance with community expectations can provide satisfaction to the community